Unmet health needs in patients with coronary heart disease: implications and potential for improvement in caring services - Asadi-Lari, M.; Packham, C.; Gray, D. (2003)
BACKGROUND: Improving the quality of health care services requires tailoring facilities to fulfil patients' needs. Satisfying patients' healthcare needs, listening to patients' opinions and building a closer provider-user partnership are central to the NHS. Few published studies have discussed cardiovascular patients' health needs, but they are not comprehensive and fail to explore the contribution of outcome to needs assessment. METHOD: A comprehensive self-administered health needs assessment (HNA) questionnaire was developed for concomitant use with generic (Short Form-12 and EuroQOL) and specific (Seattle Angina Questionnaire) health-related quality of life (HRQL) instruments on 242 patients admitted to the Acute Cardiac Unit, Nottingham. RESULTS: 38% reported difficulty accessing health facilities, 56% due to transport and 32% required a travelling companion. Mean HRQOL scores were lower in those living alone (P < 0.05) or who reported unsatisfactory accommodation. Dissatisfaction with transport affected patients' ease of access to healthcare facilities (P < 0.001). Younger patients (<65 y) were more likely to be socially isolated (P = 0.01). Women and patients with chronic disease were more likely to be concerned about housework (P < 0.05). Over 65 s (p < 0.05) of higher social classes (p < 0.01) and greater physical needs (p < 0.001) had more social needs, correlating moderately (0.32 < r < 0.63) with all HRQL domains except SAQ-AS. Several HRQL components were highly correlated with the HNA physical score (p < 0.001). CONCLUSIONS: Patients wanted more social (suitable accommodation, companionship, social visits) and physical (help aids, access to healthcare services, house work) support. The construct validity and intra-class reliability of the HNA tool were confirmed. Our results indicate a gap between patients' health needs and available services, highlighting potential areas for improvement in the quality of services